(untitled) (International journal of artificial intelligence, 2025)
This article examines the mechanism of using media technologies in developing the moral values of female students based on the spiritual heritage of the Timurid princesses. Today, the spiritual and moral development of the younger generation is important for the future of society. The historical and cultural heritage of the Timurid princesses contributed greatly to the formation of women's education. The article analyzes how media technologies are integrated into the educational process, their role and importance in developing the moral and spiritual values of female students. In the process of introducing and teaching young people the values and culture of the Timurid Empresses, innovative methods of media technologies such as video clips, online courses, and interactive materials are being used today.